9(x-2) = 5(x-1) -1 (x=3)
Answers
Answered by
0
Answer:
x=2 is your answer
hope it helps you
Attachments:
![](https://hi-static.z-dn.net/files/dec/6b3e6d069d0e0c78f332ab026ffd65d4.jpg)
Answered by
0
Answer:
• Given - 9(x-2) = 5(x-1) -1 (x=3)
• To find - value of it
• Solution -
9(x-2) = 5(x-1) -1 (x=3)
9x - 18 = 5x - 5 - x - 3
9x - 5x + x = 18 - 5 - 3
5x = 10
x = 10/5
x = 2
ADDITIONAL INFORMATION
-------☆-------☆--------☆------------
• Sign change whenever we change the side of any number.
• Only like terms are added or subtract .
• If there is no like terms then it will remain as before.
# Be brainly
Similar questions
Social Sciences,
5 months ago
Biology,
5 months ago
Math,
10 months ago
English,
10 months ago
History,
1 year ago